Safety and quality of life with maintenance olaparib plus bevacizumab in older patients with ovarian cancer: subgroup analysis of PAOLA‑1/ENGOT-ov25 - Montégut, Coline; Falandry, Claire; Cinieri, Saverio; Cropet, Claire; Montane, Laure; Rousseau, Frédérique; Joly, Florence; Moubarak, Malak; Mosconi, Anna M; Guerra-Alía, Eva M; Schauer, Christian; Fujiwara, Hiroyuki; et al. (The oncologist, 2024)
In PAOLA-1/ENGOT-ov25, the addition of olaparib to bevacizumab maintenance improved overall survival in patients with newly diagnosed advanced ovarian cancer. We describe the safety profile and quality of life (QoL) of this combination in older patients in PAOLA-1.Safety (CTCAE v4.03) and QoL (EORTC QoL Questionnaires Core 30 and Ovarian 28) data were collected. We compared safety by age (≥70 vs <70 years) in the olaparib-containing arm. QoL by treatment arm was assessed in older patients. Geriatric features, including Geriatric Vulnerability Score (GVS), were also gathered.Of 806 patients randomized, 142 were ≥70 years old (olaparib-containing arm: n = 104; placebo arm: n = 38). Older patients treated with olaparib exhibited a similar safety profile to younger patients, except for higher rates of all grades of lymphopenia and grade ≥3 hypertension (31.7% vs 21.6%, P =.032 and 26.9% vs 16.7%, P =.019, respectively). No hematological malignancy was reported. Two years after randomization, mean Global Health Status and cognitive functioning seemed better with olaparib than bevacizumab alone (adjusted mean difference: +4.47 points [95% CI, −0.49 to 9.42] and +4.82 [−0.57 to 10.21], respectively), and other QoL items were similar between arms. In the olaparib-containing arm, older patients with baseline GVS ≥ 1 (n = 48) exhibited increased toxicity and poorer QoL than those with GVS of 0 (n = 34).Among older patients in PAOLA-1, olaparib plus bevacizumab had a manageable safety profile and no adverse impact on QoL. Additional data are required to confirm these results in more vulnerable patients.(ClinicalTrials.gov Identifier: NCT02477644).